DEVELOPMENT OF TEACHER PROFESSIONALISM: PENGEMBANGAN PROFESIONALISME GURU - Cornelia Timpal (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The development of teacher professionalism is a key element in improving the quality of education. In the context of an ever-evolving education system, teachers are required to possess competencies that are not only academic but also proficient interpersonal and pedagogical skills. This research examines various strategies and programs that can be implemented to support the development of teacher professionalism, including enhancing Professional Teacher Competencies, factors causing low teacher professionalism in Indonesia, the legal foundation of the teaching profession, and teacher professionalism in enhancing education, collaborative learning, and the use of technology in teaching.. Research results show that the development of teacher professionalism is very important to enhance their abilities in teaching and educating. Age, economic factors, and culture influence teachers' motivation. Improvements in facilities and policies that support the teaching profession are necessary to enhance the quality of education. Therefore, focusing on the development of policies and recognition of the teaching profession can strengthen education as a whole. Thus, investing in the development of teacher professionalism is beneficial not only for the educators but also for the entire education ecosystem